2015
DOI: 10.15438/rr.5.4.125
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with a Modern Generation Knee System: Average 2 Years’ Follow-up

Abstract: Arthritis in the knee is a leading cause of pain and disability with total knee arthroplasty (TKA) often the treatment of choice after failure of more conservative treatments. TKA has been demonstrated to be one of the most successful procedures performed.  However, despite the good long-term survivorship rates, patient satisfaction is still an issue post TKA with over 20% of patients exhibiting patient dissatisfaction most commonly due to anterior knee pain (over 18-28% patients) and mediolateral or varus-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Our results indicated significant improvements in all clinical outcomes of the first 78 CR patients in a single surgeon series. Our results are similar to those recently reported by Paszicsnyek indicating good survivorship and positive clinical outcome of this implant [14]. In that study, the author investigated the functional outcome of the TKA by using Unity and indicated significant improvement in the outcomes measured by American Knee Society Score, Oxford Knee score and radiographic measurements.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results indicated significant improvements in all clinical outcomes of the first 78 CR patients in a single surgeon series. Our results are similar to those recently reported by Paszicsnyek indicating good survivorship and positive clinical outcome of this implant [14]. In that study, the author investigated the functional outcome of the TKA by using Unity and indicated significant improvement in the outcomes measured by American Knee Society Score, Oxford Knee score and radiographic measurements.…”
Section: Discussionsupporting
confidence: 91%
“…Traditionally, knee prosthetics with multi-radius design over the femoral component have been used; however, recent development of single-radius knee implants have shown improvements in both mechanical and clinical functions of the knee after TKA [8,13,14,18,[26][27][28][29][30]. In these implants, the biomechanical functions are improved by lengthening the extensor moment arm, providing longer distal and posterior axis, and by maintaining the isometry of the rotation and force distribution throughout the range of motion resulting in less patellar load [7,8,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations